Impact of adverse and protective childhood experiences on symptom improvement rate of anxiety disorders [analysis] - Nowak, Jonathan; Nikendei, Christoph; Dönnhoff, Ivo; Orth, Maximilian; Friederich, Hans-Christoph; Kindermann, David (Universität, 2023)
This dataset contains the complete analysis and results which were conducted for the study 'Impact of adverse and protective childhood experiences on symptom improvement rate of anxiety disorders' within one RMarkdown-Sheet.